Foundations of adult nursing - Burns, Dianne(editor) (Los Angel SAGE, 2015)
"Foundations of Adult Nursing introduces the principles, themes and issues that define what it means to be a nurse today. It explains the theory and knowledge required to develop person-centred nursing skills and explores the diverse settings and patient groups that you will encounter on your placements. Key features of the book are: A companion website with multiple choice questions for revision, and interactive glossary to test you on key terms and free SAGE journal articles to help you develop your evidence base; Stop and Think boxes which challenge you to reflect on your own practice; Discussion on the latest literature, policy and research relevant for your assignments; Case Scenarios that illustrate the realities of everyday nursing."--
Keywords: Practical nursing; Nursing; Nursing Care; Adult; Practical nursing